Low Intensity Tapping Systems and Stimulation Practices Affecting in Hevea Brasiliensis (Muell.Arg.) - Hashim, Ismail (1988)
The natural rubber industry in Malaysia is experiencing serious problems of high production costs and increasing shortage of skilled tappers. thus there is a pressing need to evolve suitable tapping systems to resolve these problems. With tais objective in mind, the suitability of various less labourintensive low-intensity tapping systems and stimulation practices are evaluated in this study.